SERVICE CHARTERS (MAKLUMAT PELAYANAN) SEBAGAI SUATU INSTRUMEN DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK OLEH PEMERINTAH - Guritno, Suryo (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2009)
The notion of service charters in terms of public service and bureaucratic reform in Indonesia is relatively a new thing compared to other countries. The issuance of Law No.25/2009 regarding Public Service has been imposing Government/Local Government to use service charters as a written statement that consists of detail obligations and promises to comply with service standard. In order the service charters to be effective and efficient, it is important for us to understand thephilosophy, concept and background of the service charters themselves. This paper is also intended to provide a picture on the concept, background, other countries? experiences, and efforts by Indonesian government to implement the service charters to enhance their service delivery. Furthermorer, this paper will discuss problems on service charter implementation and analyze the effectiveness of service charters in delivering a sound public service.